Application of Mycorrhizae Isolated from Cymbidium bicolor into the Roots of Chilli (Capsicum annum) and Onion (Allium cepa) to improve their Productivity - Denisiya, A.M.; Mikunthan, G. (Proceeding of the 3rd international conference on Dry Zone Agriculture, 2017)
Cymbidium bicolor Lindl. is an orchid, found as epiphytes on Palmyrah (Borassus flabellifer). The association of Mycorrhizae in the roots helps C. bicolor to survive during drought. Therefore, this investigation was carried out to study its compatibility and symbiosis with Chilli (Capsicum annum) and onion (Allium cepa) plants. The mycorrhizal fungi associated with the C. bicolor Lindl. is Glomus spp. which improves the seed germination and other plant quality parameters. Hence, during transplanting, plant roots can be dipped in Glomus spp. solution to initiate symbiosis in the root system. The C. bicolor plants were collected from Nelliyady, Chunnakam, Manippay, Chavakachcheri and Karaveddy in Jaffna, Sri Lanka during February-March 2017. White actively growing spongy root tips attached with C. bicolor were randomly collected. The fungi were isolated and cultured on yeast extract peptone agar medium supplemented with two to five drops of Choloromphenicol (5%) for five days at room temperature. Glomus spp. was identified by morphology and growth pattern of mycelium and produced pure culture was subjected to sub-culture. Using subculture, fungal solution was prepared. The roots of seedlings (four weeks after germination) were dipped in to fungal solution for three hours and planted according to Completely Randomized Design. Four treatments such as Glomus spp. alone, Glomus spp. with Trichoderma viride, T. viride alone and control tests were carried out and replicated five times. Plant height was measured weekly until plants were uprooted and uprooted plant’s fresh weight, plant dry weight, root coverage, number of leaves and root lets were measured. Results of the study showed that Glomus spp. alone applied chilli plants and onion plants had higher number of leaves, root length, plant height, number of root lets, plant fresh weight and, plant dry weight than other treatments (Glomus spp. + T. viride, T. viride alone and control). It was also observed that Glomus spp. and T. viride combinations gave lower result than Glomus spp. and T. viride alone treatments. Thus T. viride could have suppressed the activity of Glomus spp. From this study it can be concluded that dipping of seedlings in Glomus spp. solution will improve the productivity of chilli and onion plants.
Keywords: Cymbidium bicolor Lindl; inoculation; isolation; mycorrhizae; productivity; symbiosis